Гаус-гармата. Перспективи використання у мирних цілях - Черних, В. Д. (ХНУРЕ, 2024)
The operating principle of a Gaussian gun is considered. A list of serious disadvantages of this technology when used for military purposes is given. The possibilities of using Gaussian gun technology in astronautics, medicine, transport and scientific research are shown.
Keywords: гаус-гармата